2012
DOI: 10.1002/jssc.201100969
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of six isoflavonoids in rat plasma after administration of total flavonoid from Gegen by ultra‐HPLC‐MS/MS

Abstract: A simple, specific, and sensitive ultra-performance liquid chromatography-tandem mass spectrometry method was developed for the simultaneous determination of 3'-hydroxypuerarin, 6''-O-xylosylpuerarin, mirificin, puerarin, 3'-methoxypuerarin and daidzin in rat plasma. After the addition of methanol containing 0.1% formic acid and 10% ascorbic acid, the analytes and rutoside were obtained by protein precipitation, then separated on a Thermo Syncronis C18 column (2.1 mm × 10 cm, 1.7 μm) by gradient elution and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
2
8
0
Order By: Relevance
“…The four compounds achieved the maximum plasma concentration between 0.28 and 0.67 h. Meanwhile, the plasma concentrations of the four compounds were eliminated rapidly, within 4 h of intragastric administration. However, the pharmacokinetic parameters of 3′-methoxypuerarin were not entirely in accordance with the data reported in previous literature (Zhao, Zhao, Liu, Han, & Simultaneous, 2012). Double peaks emerged in curves of mean plasma concentration for 3′-methoxypuerarin (see Figure 3D), which is reported for the first time.…”
Section: Pharmacokinetic Analysissupporting
confidence: 87%
“…The four compounds achieved the maximum plasma concentration between 0.28 and 0.67 h. Meanwhile, the plasma concentrations of the four compounds were eliminated rapidly, within 4 h of intragastric administration. However, the pharmacokinetic parameters of 3′-methoxypuerarin were not entirely in accordance with the data reported in previous literature (Zhao, Zhao, Liu, Han, & Simultaneous, 2012). Double peaks emerged in curves of mean plasma concentration for 3′-methoxypuerarin (see Figure 3D), which is reported for the first time.…”
Section: Pharmacokinetic Analysissupporting
confidence: 87%
“…Our study demonstrated that protein precipitation can be used to analyze plasma samples from humans ingested low doses of anthocyanins. Protein precipitation as the only sample preparation procedure has been successfully used to analyze isoflavonoids (Zhao, Zhao, Liu, Han, & Yu, ), flavanone (Liu, Xu, Zhang, Song, & Tian, ) and puerarin (Prasain et al, ) in rat plasma or serum with HPLC‐MS/MS. For the analysis of small molecules, plasma protein precipitation was commonly facilitated by adding an acid.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Wang et al [20] presented the LC-MS/MS method with a comparably higher sensitivity of relatively LLOQ 0.39 ng/mL than other studies [9,10,18,19] with a LLOQ of 2-18.6 ng/mL for puerarin. Also, further studies provided information about the simultaneous determination of puerarin and daidzein in rat plasma by using LC-MS [2], UPLC-MS [21] or UPLC-MS/MS [22], serum [23] and urine [24] in humans by using HPLC.…”
Section: Introductionmentioning
confidence: 99%